A new genus and new species of Nearctic Therevidae (Insecta: Diptera) from Southern New Mexico - Webb, Donald W. (Zootaxa, 2007)
A new genus of Nearctic Therevidae, Spinalobus gen. nov. is described with illustrations of its genitalia and distribution information. A key is provided to identify the genus. The placement of this genus within the subfamily Therevinae is discussed.